Penetrating trauma causing cerebrospinal fluid leak without nerve root damage. (14th May 2018) - Carpenter, Holly; Hurndall, Katherine-Helen; Asokan, Ajay K; Fernandes, Roland
Abstract : A 19-year-old man with a stab injury to the lower back presented with no focal neurology or haemodynamic instability. He complained of a headache that was improved by lying flat and underwent imaging to look for damage to local structures. He was found to have air in his intraspinal space. Initially this case was managed conservatively; however, 2 weeks after discharge, he presented with cerebrospinal fluid leak from his wound. This was managed with neurosurgical intervention and watertight closure of fascia. There were no further complications.